Synthesis and characterization of the Co(II) and Ni(II) complexes of 1, 3, 4-thiadiazole-derived ketones and secondary alcohols: thermal and magnetic properties. Issue 15 (17th December 2021) - Erdogan, Melih; Kiymaz, Kubra; Tahtaci, Hakan; Uysal, Saban
Abstract: Compounds containing both ketone and amide carbonyl groups were reduced with sodium borohydride (NaBH4 ). In this way, secondary alcohols, which are very important compounds for the synthesis of drugs, agricultural chemicals, food chemicals, and other chemicals, were obtained with regioselectivity. To do this, the starting compound 2-(5-amino-1, 3, 4-thiadiazol-2-yl)thio)-1-(3, 4-dichlorophenyl)ethanone (3 ) was obtained. Subsequently, 10 ketone derivatives (5a-j ) were synthesized from the reaction of 3 with the appropriate substituted acyl halide derivatives (4a-j ). Then, secondary alcohol derivatives (6a-j ), which came from the regioselective reduction of the ketone derivatives (5a-j ), were synthesized with NaBH4 . The molecular structures of ketone and alcohol derivatives were elucidated using 1 H NMR, 13 C NMR, FTIR, and MS. In the last step of the study, binuclear metal complexes of all alcohol and ketone derivatives were synthesized in DMF and characterized using FTIR and MS. The magnetic properties and thermal stability of these complexes were investigated using magnetic susceptibilities and determined using a Gouy magnetic susceptibility apparatus and a TGA analyzer, respectively. The complexes are distorted octahedral low-spin ( S = 3/2) Co(II) and distorted octahedral ( S = 1) Ni(II). Finally, the metal ratios of the complexes were determined by using ICP-AES. Graphical Abstract: UF0001